An Exploratory Study Into Stakeholder Marketing: An Investigation Into Stakeholder Preferences With Respect To Corporate Identity and Environmental Marketing - Isherwood, James Allan Donald (2008)
This dissertation was designed as an exploratory study into the workings of a company's stakeholders. The aim of the research was to gain an insight into a company's stakeholder preference and to establish what sort of marketing is most important to them. For the purposes of the research, two main characteristics were chosen to be investigated, a company's corporate identity and a company's environmental positioning. Obviously due to certain limitations that were placed on the dissertation, it was impossible to investigate all of a company's stakeholders preferences, so a select group of three of a company's stakeholders were chosen, these are a company's potential customers, employees and investors, arguably three of the most important.